“Our connection makes us stronger”: Inuit youth’s strategies to feel comfortable in Ottawa - Vaudry, Stéphanie (Études/Inuit/Studies, 2016)
This paper focuses on challenges young Inuit adults face in everyday life in the city and the coping strategies they have developed. For research participants, being “connected” with the world(s) surrounding them appears to be central to how they feel and orientate themselves in the city. Connectedness, for these young Inuit, translates into close and significant relationships with people, ancestors, future generations, objects, animals, and nature, which are elements of the Inuit universe of meanings and, more broadly, belong to Indigenous universes. Therefore, being comfortable is linked to the maintenance of harmonious relationships with these different agents. As we will see, urban milieus, like Ottawa, belong to a universe of meanings to which Inuit youth are not always accustomed. Nevertheless, through their agency, they develop strategies to establish relationships within the city, enabling themselves to become acquainted with the urban world and its inhabitants. As Ottawa hosts a large Inuit community, the urban challenges that they face can be mitigated as they participate in Inuit worlds.